Wnt Signalosome Assembly by DEP Domain Swapping of Dishevelled - Gammons, Melissa V. (Cell Press, 2016)
Extracellular signals are often transduced by dynamic signaling complexes (“signalosomes”) assembled by oligomerizing hub proteins following their recruitment to signal-activated transmembrane receptors. A paradigm is the Wnt signalosome, which is assembled by Dishevelled via reversible head-to-tail polymerization by its DIX domain. Its activity causes stabilization of β-catenin, a Wnt effector with pivotal roles in animal development and cancer. How Wnt triggers signalosome assembly is unknown. Here, we use structural analysis, as well as biophysical and cell-based assays, to show that the DEP domain of Dishevelled undergoes a conformational switch, from monomeric to swapped dimer, to trigger DIX-dependent polymerization and signaling to β-catenin. This occurs in two steps: binding of monomeric DEP to Frizzled followed by DEP domain swapping triggered by its high local concentration upon Wnt-induced recruitment into clathrin-coated pits. DEP domain swapping confers directional bias on signaling, and the dimerization provides cross-linking between Dishevelled polymers, illustrating a key principle underlying signalosome formation.